ANALISIS KESESUAIAN ANTARA STRATEGI SDM DENGAN STRATEGI BISNIS PADA UNIKA SANTO THOMAS MEDAN - Tinambunan, Anitha Paulina (UNIKA Santo Thomas, 2021)
Human resource strategy is part of the business strategy implementation process. Certain business strategies require specific competencies and personal characteristics. Human resource strategy is a derivation of changes in business strategy or company strategy.This research is intended to know:1) What is the stated business strategy of the Catholic University of Saint Thomas Medan? ; 2) What is the human resource strategy implemented by the Catholic University of Saint Thomas Medan? ; 3) .Is the human resource strategy implemented in accordance with the business strategy of the Catholic University of Saint Thomas Medan? Based on the results of the analysis, it is known that the human resource strategy is in accordance with the business strategy of the Catholic University of Saint Thomas Medan. This can be proven by the following data: a) In 1984-2000, the Corporate strategy was a Growth strategy by conducting Market Development and Product Development. The Business strategy is Defender while the Human resource strategy is Club; b) In 2001-2015, the Corporate strategy is Growth (Product development) and Retrenchment (Turnaround). Its Business strategy is Defender and Reactor, while its Human resource strategy is Club and Fortress; c) In 2016-present, the Corporate strategy is Stability and Growth (Market development & Product development). The Business strategy is Analyzer and the Human resource strategy is Academy.